In Splendor of Virtues: Bathing of Susanna by Tintoretto and the Symbolism of the Wedding Jewelry Set - Savchenkova, Anna A. (Actual Problems of Theory and History of Art, 2024)
. It may seem that in the painting Bathing of Susanna kept in Vienna, Jacopo Tintoretto portrays the Old Testament heroine as an embodiment of temptation. But is she revealed as frankly as we imagine? The naked woman is depicted in paired bracelets and pearl earrings, a necklace, while a bone comb, a long silver hairpin, an embroidered wide belt, a miniature box are placed all around her. We assume that the listed jewelry is endowed with a semantic and symbolic role in the program of the canvas. Indeed, all the listed jewelry made up the wedding set of a Venetian bride of the 16th century which was given to her by her future husband. Later, the girl appeared in it as a future wife and hostess and kept the ceremonial attire for her entire life. Consequently, the depiction of the wedding jewelry in Tintoretto’s painting reflects the entire story of Susanna and the set should be seen as a promise of a happy ending: the danger that threatened Susanna will be resolved by the triumph of her virtue. The interpretation of the plot itself in the eyes of the contemporaries was probably not obscene, since the naked heroine was "protected" by jewelry that reminded of her devotion to her husband.
Keywords: Jacopo Robusti; Tintoretto; Renaissance; Venice; Susanna and the Elders; wedding jewelry set; Susanna bathing; applied arts